Estrutura química para o 9º ano do ensino fundamental: uma proposta de ensino envolvendo tecnologia digital com vistas à aprendizagem significativa - Bacega, Taiane (2020)
The XXI century has been target of significant changes in Education, especially regarding the inclusion of digital technologies for teaching methodologies used in schools. To innovate in teaching activity using diversified educational resources, in particular those generated in the technological landscape that we are leaving, it seems to be an appropriate path. This alignment with the actualization requests in the teaching process can be a driving factor to increased the student interaction with the school environment, providing learning and development of more participative attitude. Based on these considerations, the objective of this work was to elaborate and apply a Potentially Meaningful Teaching Unit (PMTU), in order to perceive signs of significant learning of the concepts of chemical structure for the 9th grade of elementary school. The guiding question of the research was: “How does the teaching process develop from the implementation of a PMTU based on the diversification of digital resources for teaching chemical structure with a view to meaningful learning?”. The research, developed following the qualitative approach, is characterized as an action research. The theoretical basis was David Ausubel's MLT - Meaningful Learning Theory. The PMTU, which is the elaborated educational product, was constructed searching to incorporate digital technologies along the didactical intervention, using smartphones and diverse applications such as: Socrative, eReader, RApp Chemistry, PhET, Coogle e Soundcloud, as the basic resources. It was developed with 18 students of 9th grade from a private school in the city of Tapejara - RS. The data were constituted by pre and post-test analysis, individual summative assessment, collaborative activities performed individually and in groups, and the records made by the researcher in the logbook during the proposal. It was possible to verify learning evidences in the majority students in relation to chemistry bonds and molecular geometry contents by the results obtained in specific activities listed for analysis of this parameter. However, in the electronic distribution the expected advances were not the expected ones. Regarding to digital resources utilization it was possible to observe that they streamline the classes, providing, during the process, an effective interaction (student-student; student-teacher; student-instructional material; student-resource). In general, the students evaluated positively the use of digital technologies, in particular, the RApp Chemistry, app of augmented reality used during the contents development. The educational product that accompanies this study, the PMTU elaborated, is available in